2000
DOI: 10.1103/physrevd.62.044005
|View full text |Cite
|
Sign up to set email alerts
|

Warp drive space-time

Abstract: In this paper the problem of the quantum stability of the two-dimensional warp drive spacetime moving with an apparent faster than light velocity is considered. We regard as a maximum extension beyond the event horizon of that spacetime its embedding in a three-dimensional Minkowskian space with the topology of the corresponding Misner space. It is obtained that the interior of the spaceship bubble becomes then a multiply connected nonchronal region with closed spacelike curves and that the most natural vacuum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Finally, spacetimes where timelike curves can travel along superluminal (as described by a distant observer) trajectories can be used to generate closed timelike curves. The Alcubierre warp drive [1] can be used to generate CTCs [4], [8]; as can the Krasnikov tube [5], [12].…”
Section: A Exotic Spacetimesmentioning
confidence: 99%
“…Finally, spacetimes where timelike curves can travel along superluminal (as described by a distant observer) trajectories can be used to generate closed timelike curves. The Alcubierre warp drive [1] can be used to generate CTCs [4], [8]; as can the Krasnikov tube [5], [12].…”
Section: A Exotic Spacetimesmentioning
confidence: 99%
“…Not surprisingly, warp drives also engender the appearance of CTCs. 31,82 Technical fixes have been proposed to mitigate against the formation of CTCs in and around the warp bubble by performing some minor modification(s) to the warp field geometry. However, since we previously showed that warp drives may not be technologically practical to implement, we will not consider this issue any further.…”
Section: Time Machines and Ftl Causality Issuesmentioning
confidence: 99%
“…Reminiscence of an Event Horizon: The appearance of an event horizon becomes evident in the 2-dimensional model of the Alcubierre space-time, with ρ = 0 [10,11,12]. The axis of symmetry coincides with the line element of the spaceship.…”
Section: Interesting Aspects Of the Alcubierre Spacetimementioning
confidence: 99%